The Association between Depression and Leptin is Mediated by Adiposity - Morris, Alanna A. (2012)
OBJECTIVE: Depression and obesity share overlapping psychosocial and pathophysiological etiologies. Animal models suggest that impaired leptin production, or leptin resistance, may contribute to depression. The link between leptin and depression could be mediated by obesity, which is more common in depression and increases leptin production. METHODS: We administered the Beck Depression Inventory II (BDI-II) to 537 participants (mean age 51, standard deviation 9 years, 49% African American, 61% female) enrolled in the Morehouse-Emory Partnership to Eliminate Cardiovascular Health Disparities (META-Health) study. BDI-II scores of 0–13 indicated minimal to no depression, 14–19 mild depression, and 20–63 moderate to severe depression. Levels of leptin were examined as continuous, log-transformed values. RESULTS: Participants with moderate to severe depression had higher levels of leptin (median 37.7, interquartile range [17.6–64.9] ng/mL) than those with mild depression (22.9 [7.0–57.9] ng/mL) or minimal to no depression (19.8 ng/mL, [7.8–39.1], p=0.003). Participants with moderate to severe depression had higher body mass index (BMI) than those with mild or minimal depression (33±8 vs. 31±9 vs. 29±7 kg/m(2), p<0.001). After multivariate adjustment for age, gender, race, smoking, history of hypertension and diabetes, blood pressure, lipids, and CRP, the BDI-II score remained a significant predictor of leptin levels (β=0.093, p=0.01). Further adjustment for BMI eliminated the association between the BDI-II score and leptin (β=0.03, p=0.3). Adjusting for waist circumference in place of BMI revealed similar findings. CONCLUSION: The association between depression and leptin appears to be mediated by increased adiposity in depressed individuals. Leptin may represent a pathway through which obese individuals may develop depression, or a common mechanism leading to both depression and obesity.